Reliability analysis on digital literacy skills, digital financial inclusion and socio-economic development among B40 in Selangor - Mohammad Nazim, Naily Irdina Iman; Mohamed Shuhidan, Shamila; Hashim, Husain; Baharuddin, Mohammad Fazli; Winoto, Yunus; Rahman, Mohd Saiful (Faculty of Information Management, 2025)
This study aims to examine the validity of metrics used to evaluate the digital literacy skills, digital financial inclusion, and socio-economic development of the B40 group in Selangor. This study looks at how these variables relate to one another and how interdependent they are. The questionnaire consists of six sections, including demographics, ICT skills, socio-economic development, digital literacy, digital financial inclusion, challenges and suggestions. The B40 groups in Selangor are intended to be included in the sample. A 56-item questionnaire was created after the literature was reviewed. The instrument was examined by a group of subject-matter experts to guarantee the validity, reliability, and normalcy of the results. Thirty respondents participated in a pilot study that was also carried out. Data was analyzed using statistical software. The results of the analysis show that there are no anomalies in the data and that the instrument is reliable.